Investigation of truncated replication protein mutant of Canine Circovirus: synergistic interaction with Feline Panleukopenia Virus - Li, Suyao; Xin, Jialiang; Peng, Yi; Liu, Haifeng; Zhou, Ziyao; Zhong, Zhijun; Fu, Hualin; Yang, Min; Li, Wancheng; Wu, Ruihu; Peng, Guangneng (Frontiers in Veterinary Science, 2025)
BackgroundCanine Circovirus (CanineCV) is a non-enveloped, single-stranded circular DNA virus in the Circoviridae family, known to cause respiratory and diarrheal diseases in dogs. It can also lead to immune suppression, which may worsen symptoms during co-infection. The virus’s Replication (Rep) and Capsid (Cap) proteins play crucial roles in its life cycle. This study explores a novel truncated Rep’ mutant of CanineCV and examines its impact on feline health when co-infected with Feline Panleukopenia Virus (FPV).MethodWe constructed and validated clones and plasmids for CanineCV/ SC49 (which carries the normal Rep gene) and CanineCV/SC50 (which carries the truncated Rep’gene). Virus particles were visualized using transmission electron microscopy (TEM), while quantitative polymerase chain reaction (qPCR) assessed viral load. Additionally, we examined the effects of Rep and Rep’ proteins on cellular viability, their roles in FPV replication, and the host interferon type I (IFN-I) response.ResultsThe Rep’ protein significantly enhances the cytotoxicity of CanineCV against the F81 cell line, outperforming the Rep protein in this regard. However, when assessing the proliferation-promoting effects on FPV, both proteins demonstrated positive effects, but Rep exhibited a significantly greater impact than Rep’ Additionally, qPCR analysis revealed that Rep has a stronger inhibitory effect on the expression of IFN-α, IFN-β, MxA, and ISG15 genes compared to Rep’.ConclusionThis study underscores the dual roles of Canine Circovirus in modulating host cell viability. On one hand, it enhances the replication of co-infecting viruses; on the other hand, it suppresses the host’s antiviral responses. These findings provide valuable insights into the pathogenic mechanisms of Canine Circovirus.